ANALISIS FAKTOR – FAKTOR YANG BERPENGARUH TERHADAP PRODUKSI USAHATANI UBI JALAR DI KELURAHAN HINEKOMBE DISTRIK SENTANI KABUPATEN JAYAPURA - Sanggenafa, Nova Fida (Institute of Computer Science (IOCS), 2024)
This research aims to analyze the factors that influence sweet potato farming production in Hinekombe Village, Sentani District, Jayapura Regency. Factors studied include land area, labor, fertilizer use, and farmer experience. The approach used is quantitative with a multiple regression analysis method, which was chosen because it is able to test the influence of several independent variables simultaneously on the dependent variable, namely the level of sweet potato production. Data was collected through direct interviews using questionnaires with 56 farmers with production above 500 kg per harvest. Sample selection was based on certain criteria to ensure data relevance and optimal representation of production conditions. The research results show that land area and fertilizer use have a significant influence on sweet potato production, while labor and farmer experience do not have a significant influence. These findings provide strategic implications in efforts to increase sweet potato production through optimizing land use and production inputs.